Mesenchymal stem cell-derived exosomes can alleviate GVHD and preserve the GVL effect in allogeneic stem cell transplantation animal models - Jiang, Yan; Zhao, Jie; Wang, Minghui; Huang, Fang; Li, Jiaqi; Liu, Rui; Wan, Jiangbo; Hao, Siguo (Frontiers in Immunology, 2023)
Background: Mesenchymal stem cells (MSCs) can alleviate graft versus host diseases (GVHD) in hematopoietic stem cell transplantation (HSCT). MSCs-derived exosomes (MEXs) can mirror the biological function of their parent cells. Whether MEXs could alleviate GVHD like their parent cells or not is unclear. In this study, we investigate the effects of MEXs on GVHD and graft versus leukemia (GVL) effect in vitro and in HSCT animal model. Method: MSCs were produced using the bone marrow MNCs and MEXs were separated from the supernatants of MSCs. Electron microscopy, western blot, and nanoparticle tracking analysis (NTA) were used to determine the characteristics of MEXs. The immunomodulatory function of MEXs and their effects on GVHD and GVL were examined in vitro and in vivo. Result: Like other cell type derived exosomes, our data revealed that MEXs were also disc-shaped vesicles with a diameter of 100–200 nm under the electron microscopy and were positive for the exosomal hallmark proteins. MEXs can notably inhibit expression of costimulatory molecules and functional cytokine secretion of dendritic cells (DCs). Meanwhile, MEXs can exert suppressive effects on T lymphocyte proliferation and activation. Moreover, MEXs also can encourage the polarization of macrophages toward the M2 type. In animal HSCT models, MEXs can promote the differentiation of Treg cells in spleens, decrease the GVHD score, increase the survival rate of mice, and preserve the cytotoxic antileukemia effects of CD8+ T lymphocytes from recipient mice. Conclusion: These findings showed that MEXs exert their effects by inhibiting the immunomodulatory function of DCs, macrophages, and T lymphocytes. In the animal model, MEXs ameliorate the clinical symptoms of GVHD, while maintaining the antitumor effects of CD8+ T lymphocytes. Therefore, it can be inferred that MEXs can separate GVHD from GVL in HSCT. Our study suggests that MEXs has a broad clinical application potential in the prevention and treatment of GVHD in HSCT in the near future.